PERMBERDAYAAN POSYANDU REMAJA PADA KADER KESEHATAN DESA JATI KALANG PRAMBON SIDOARJO - Nurul Azizah; Paramtha Amelia Kusumawardani; Rafhani Rosyidah; Ratna Dwi Jayanti (LPPM Universitas PGRI Adi Buana Surabaya, 2023)
Adolescence is a period of transition from children to adults, there are many changes experienced by adolescents, causing various kinds of problems, including reproductive health and psychology. The posyandu activities in Jati Kalang village, Prambon Sidoarjo didn’t run optimally. The community service activities are aimed at optimizing youth posyandu activities. This activity was attended by 12 health cadres and 33 adolescent organizations. This activity starts with the formation of health cadres by involving cadres and youth in Jati Kalang village and joining by workshop and training. The result of this activity indicates that the youth posyandu activities in Jati Kalang have been active again, through the formation of adolescent health cadres, and the holding of workshops and training health cadres on government programs related to youth posyandu, prevention of anemia, adolescent nutritional, adolescent reproductive health counselling and implementation five table system, as well as the delivery of medical equipment to support youth posyandu facilities. Youth posyandu activities held every 2 months at Jati Kalang village hall Prambon Sidoarjo. Conclusion: The adolescent of Jati Kalang village were very enthusiastic to participate in the youth posyandu activities. The series of activities had run fluent and received a good response from the community.